Peripherally-administered amphetamine induces plasticity in medial prefrontal cortex and nucleus accumbens in rats with amygdala lesions: implications for neural models of memory modulation - McDonald, Robert J.; Hong, Nancy S.; Germaine, Carlie; Kolb, Bryan (Frontiers in Behavioral Neuroscience, 2023)
The amygdala has been implicated in a variety of functions linked to emotions. One popular view is that the amygdala modulates consolidation in other brain systems thought to be mainly involved in learning and memory processes. This series of experiments represents a further exploration into the role of the amygdala in memory modulation and consolidation. One interesting line of research has shown that drugs of abuse, like amphetamine, produce dendritic changes in select brain regions and these changes are thought to be equivalent to a usurping of normal plasticity processes. We were interested in the possibility that this modulation of plasticity processes would be dependent on interactions with the amygdala. According to the modulation view of amygdala function, amphetamine would activate modulation mechanisms in the amygdala that would alter plasticity processes in other brain regions. If the amygdala was rendered dysfunctional, these effects should not occur. Accordingly, this series of experiments evaluated the effects of extensive neurotoxic amygdala damage on amphetamine-induced dendritic changes in the nucleus accumbens and prefrontal cortex. The results showed that rats with large lesions of the amygdala showed the normal pattern of dendritic changes in these brain regions. This pattern of results suggests that the action of not all memory modulators, activated during emotional events, require the amygdala to impact memory.